The Values of Feminism in the Novel Mata Dan Nyala Api Purba by Okky Madasari - Rahma, Yadia; Sarwiji Suwandi; Edy Suryanto (Jurnal Sastra Indonesia, 2025)
Feminist values refer to the basic principles that underlie the feminist movement and thought. These values emphasize gender equality, justice, and women's empowerment in various aspects of life. This qualitative study analyzes Okky Madasari's novel "Mata dan Nyala Api Purba" (Eyes and Ancient Flames). Data were obtained through text content analysis using a purposive sampling technique. Document analysis was used for data collection, while validity was maintained through triangulation of sources and methods. The analysis was conducted interactively to gain a deeper understanding of the liberal feminist values within the work. The analysis shows that the values of equal rights and opportunities are the most dominant aspect in the novel, with a frequency of 32%. This is reflected in the representation of female characters who have equal access and opportunities to men, both in private and public spaces. The value of individual independence is also prominent (25%), depicting women as figures capable of making decisions and acting independently. Furthermore, individual freedom and life choices are recorded at 21%, demonstrating the space for female characters to determine their own direction. Public participation reaches 14%, demonstrating women's involvement in the social and political spheres. Meanwhile, rejection of traditional gender roles emerged at 7%, demonstrating resistance to stereotypes that limit women's roles in society. Overall, the five components of liberal feminist values in this novel demonstrate that Mata dan Nyala Api Purba (The Eyes and the Ancient Flame) is imbued with the spirit of emancipation and gender equality. Therefore, this literary work can be used as a learning resource to enrich understanding of feminist values within the context of Indonesian culture.